The Nexus Between Rates of Return on Deposits of Islamic Banks and Interest Rates on Deposits of Conventional Banks in a Dual Banking System: A Cross Country Study - Abdurraheem, Abdulazeez Adewuyi; Asmadi, Mohamed Naim (International Journal of Economics and Financial Issues, 2016)
The paper investigates the existence of a long-run relationship between conventional interest rates and rates of return on deposit of Islamic banks in the contemporary dual banking systems on a cross-country basis. The study employs ARDL (Autoregressive Distributed Lag) modeling approach to cointegration analysis. The study finds the existence of the long run relationship between rates of return on deposits of Islamic banks and interest rates on deposits of conventional banks during the period 2007 – 2015. The study also finds a bidirectional causal relationship running between rates of return on deposits of Islamic banks and conventional interest rates. The study statistically provides empirical insight into the relationship between the rate of return on deposits of Islamic banks and the conventional interest rate on a cross-country basis using an ARDL model.